2021
DOI: 10.1007/s00268-021-06012-8
|View full text |Cite
|
Sign up to set email alerts
|

Long‐Term Trends and Predictors of Medical Resource Utilization and Medical Outcomes in Inguinal Hernia Repair: A Nationwide Cohort Study

Abstract: Background Few studies have comprehensively and systematically analyzed nationwide samples. This study purposed to explore temporal trends and predictors of medical resource utilization and medical outcomes in these patients to obtain data that can be used to improve healthcare policies and to support clinical and administrative decision‐making. Methods This study used nationwide population data contained in the Longitudinal Health Insurance Database of Taiwan. The 14,970 inguinal hernia repair patients were e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
7
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(7 citation statements)
references
References 29 publications
0
7
0
Order By: Relevance
“…The unit of statistical analysis in this Taiwanese study was the individual elderly patient [26,27]. Sample size calculations determined that, for a power of 0.80, a minimum sample of 120 study participants was needed with an alpha of 0.05 [28].…”
Section: Discussionmentioning
confidence: 99%
“…The unit of statistical analysis in this Taiwanese study was the individual elderly patient [26,27]. Sample size calculations determined that, for a power of 0.80, a minimum sample of 120 study participants was needed with an alpha of 0.05 [28].…”
Section: Discussionmentioning
confidence: 99%
“…In the review of the literature on the relationship between pre-operative symptomatology and post-operative outcomes, it was observed that the vast majority of studies have not researched a specific symptomatology, but include a heterogeneous group of signs and symptoms, contrasting them with divergent results [ [11] , [12] , [13] , [14] , [15] , [16] , [17] , [18] , [19] , [20] , [21] ]. Evaluating the level of evidence in descending order (from highest level to lowest level of available evidence) on pre-operative symptomatology and its relationship with outcomes, only one systematic review [ 11 ], one clinical trial [ 12 ] and a considerable number of observational studies were found [ [13] , [14] , [15] , [16] , [17] , [18] , [19] , [20] ]. Reinpold W [ 11 ] conducted a systematic review where he evaluated risk factors for the development of chronic pain after inguinal hernia repair, showing that intense pre-operative pain, alteration in the patient's mood and history of chronic pain regardless of its cause, are associated with the onset and persistence of this chronic pain [ 11 ].…”
Section: Pre-operative Symptomatology Functional Outcomes and Quality...mentioning
confidence: 99%
“…Romain et al [ 16 ], Mier et al [ 17 ] and Kuo et al [ 18 ], conducted prospective studies with the aim of evaluating the long-term quality of life of patients with inguinal hernia, according to pre-operative symptomatology, finding similar results, on the prevalence of pre-operative pain (>25% of cases) vs. pain at two years (<5% of cases), and predominantly this pain was moderate [ [16] , [17] , [18] ]. Similarly, quality of life is restored more quickly in those who have no pain or very mild pain (p = 0.048) [ 17 ].…”
Section: Pre-operative Symptomatology Functional Outcomes and Quality...mentioning
confidence: 99%
See 2 more Smart Citations